The Impact of Online Game Addiction on Children’s Social Interaction and Academic Performance - Ade Aspandi; Aip Syarifudin; Muhammad Azhar Muttaqin (Journal of General Education and Humanities, 2026)
The phenomenon of online game addiction among youth has emerged as a critical concern in today’s digital society, significantly influencing social interaction and educational outcomes. This study aims to examine the psychological and sociological effects of excessive online gaming through a systematic literature review. Data were collected from 32 scholarly articles and undergraduate theses published between 2013 and 2025, and analyzed to identify recurring behavioral and academic patterns. The findings indicate that approximately 70% of the reviewed studies reported a decline in face-to-face communication, emotional sensitivity, and empathy among young gamers. Moreover, 65% of the sources highlighted academic disengagement, decreased motivation to learn, and lower performance levels. Prolonged gaming also correlates with heightened stress, anxiety, and irregular sleep cycles, demonstrating the multifaceted nature of this behavioral issue. These impacts extend beyond the individual, disrupting family relations and school environments. The study recommends integrated interventions involving parental monitoring, educator participation, and balanced digital policy implementation to foster responsible gaming habits. This research contributes to a deeper understanding of online game addiction by integrating perspectives from social learning and behavioral addiction theories, providing a conceptual framework for future studies on youth digital behavior.